Synthesis and characterization of novel poly[4‐phenyl‐3‐(thiophen‐3‐ylmethyl)‐1H‐1, 2, 4‐triazole‐5(4H)‐thione]. Issue 6 (8th January 2020) - Trung, Vu Quoc; Linh, Nguyen Ngoc; Duong, Tran Thi Thuy; Chinh, Nguyen Thuy; Linh, Duong Khanh; Hung, Ha Manh; Oanh, Doan Thi Yen
Abstract: By the oxidative coupling polymerization, a new polythiophene containing 1, 2, 4‐triazole heterocyclic group was synthesized in chloroform solvent using iron(III) chloride as an oxidant catalyst. Analyses of infrared (IR) and ultraviolet–visible (UV‐Vis) spectra confirmed that the polymerization reaction took place and the absorption band at 469 nm characterized for π–π* transition in the conjugated polymer. Morphology and surface properties of the polymer were studied by field emission scanning electron microscopy (FESEM). Polymer had relatively uniform size distribution. Based on thermal gravimetry analysis (TGA), polymer is without impurities and has an adequate thermal stability in air atmosphere when completely decomposed at 500 o C. The polymer exhibited fluorescence emissions at 596 nm corresponding to the conjugated chain in polymer. Polymer exhibited a good electrical conductivity in the undoped state (around 1.37E–7 S.cm ‐1 at 1 MHz).